1
$\begingroup$

I am normally good at solving trigonometry sums. However I stumbled upon this and could not figure out how to do it. I solved a few lines and then I got stuck. If anyone can teach me how to prove the equation, I'll be highly grateful.

If $\cos^2 A- \sin^2 A = \tan^2 B$, prove that $\cos^2 B - \sin^2 B = \tan^2 A$

So here is what I did:

$\cos^2 B = \dfrac{\sin^2 B}{\cos^2 A - \sin^2 A}$

So going by the second R.T.P,

$\cos^2 B - \sin^2 B = \dfrac{\sin^2 B}{\cos^2 A - \sin^2 A} - \sin^2 B$

which unfortunately ends up nowhere close to the original proving required.

Thanks for any possible help!

$\endgroup$
1
$\begingroup$

Add 1 to both sides, and massage the result.

$\endgroup$
0
$\begingroup$

$$ \cos 2A /1 = \sin^2 B/ \cos^2 B = \tan^2 B \tag 1$$

Apply Componendo Dividendo Rule

$$ \dfrac{1- \cos 2A}{1+ \cos 2A}= \dfrac{\cos^2 B- \sin^2 B}{1} $$

$$\tan^2 A = \cos 2 B $$

$$ \cos 2 B = \tan^2 A. \tag 2 $$

$\endgroup$
0
$\begingroup$

$$\tan^2B=\cos^2 A- \sin^2 A$$

$$\iff\dfrac{\sin^2B}{\cos^2B}=\dfrac{\cos^2 A- \sin^2 A}{\cos^2 A+\sin^2 A}$$

Apply Componendo & Dividendo

$\endgroup$
0
$\begingroup$

From $\cos^2A-\sin^2A=\tan^2B$ you get $$ \cos^2A=\frac{1+\tan^2B}{2}=\frac{1}{2\cos^2B} $$ and $$ \sin^2A=\frac{1-\tan^2B}{2}=\frac{\cos^2B-\sin^2B}{2\cos^2B} $$ Thus $$ \tan^2A=\frac{\cos^2B-\sin^2B}{2\cos^2B}\,2\cos^2B $$

$\endgroup$
0
$\begingroup$

The equation can be rewritten

$$(\cos^2(A)-(1-\cos^2(A)))\cos^2(B)=\sin^2(B)$$

or after simplification

$$2\cos^2(A)\cos^2(B)=1,$$

which is perfectly symmetrical.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.